Common fixed points for weak compatible maps in fuzzy metric spaces - sharma, praveen kumar; choudhary, sanjay; wadhwa, kamal (International Journal of Applied Mathematical Research, 2012)
In this note we shall prove common fixed point theorems for four mappings under weak compatible condition in the setting of fuzzy metric space, fuzzy 2-metric space, and fuzzy 3-metric spaces. Our results generalize the results of Singh, Jain and Jain.